Nephrotoxicity in advanced thyroid cancer treated with tyrosine kinase inhibitors: An update. (December 2021) - Nervo, Alice; Retta, Francesca; Ragni, Alberto; Piovesan, Alessandro; Mella, Alberto; Biancone, Luigi; Manganaro, Marco; Gallo, Marco; Arvat, Emanuela
Highlights: Tyrosine kinase inhibitors (TKIs) are employed in advanced thyroid cancer patients. Renal adverse events (RAEs), especially proteinuria, are frequently reported. VEGF pathway inhibition seems to be involved in the development of RAEs. TKIs-treated patients should be monitored with serum creatinine and urine dipstick. In case of RAEs from TKIs a multidisciplinary approach is recommended. Abstract: Over the past decade, the prognosis of advanced thyroid cancer (TC) patients has dramatically improved thanks to the introduction of tyrosine kinase inhibitors (TKIs). Despite their effectiveness, these drugs are burdened with several side effects that can negatively affect quality of life and compromise therapy continuation. Among renal adverse events (RAEs), proteinuria is the most frequently reported in clinical trials and real-life experiences, especially during treatment with lenvatinib or cabozantinib. This peculiar toxicity is commonly associated with targeted therapies with anti-angiogenic activity, even if the mechanisms underlying its onset and progression are not entirely clear. RAEs should be early recognized and properly managed to avoid renal function worsening and life-threatening consequences. Aiming at providing a comprehensive summary that can help clinicians to identify and manage TKIs-related RAEs in TC patients, we reviewed the current evidence about this topic, from pathogenesis and potential risk factors to diagnosis and treatment.